INTERJEIÇÕES E INVOCAÇÕES: A ORDEM DOS CONSTITUINTES EXCLAMATIVOS NO PORTUGUÊS BRASILEIRO | INTERJECTIONS AND INVOCATIONS: THE ORDER OF EXCLAMATIVE CONSTITUENTS IN BRAZILIAN PORTUGUESE - MOREIRA, JULIANA COSTA (2017)
O presente artigo tem como objetivo descrever e analisar a ordem de constituintes exclamativos, como as interjeições Ah!, Oh!, Credo!, dentre outras; e invocações, como Meu Deus!, Senhor!, Nossa Senhora! no Português Brasileiro. Utilizando exemplos, foi possível demonstrar a posição de ocorrência das interjeições e das invocações. Na sequência, adotando-se a proposta de Hill (2007, 2014), apresentamos a derivaçãodas construções com estes constituintes.Abstract: This paper aims to describe and analyze the order of exclamative constituents, such as the interjections Ah!, Oh!, Credo!, among others; and invocations, such as Meu Deus!, Senhor!, Nossa Senhora! in Brazilian Portuguese. Through the analysis ofexamples, it is possible to demonstrate the position of interjections and invocations. Next, adopting Hill’s proposal (2007, 2014), we present the derivation for constructions with these constituents.